Equines as Experimental Models: A Review of Their Use in Therapy, Antivenom Production, and Sports - , Ananda Silva Silveira; , Luana Mikaela Gomes Rangel; , José Sérgio Herculano Gomes da Silva; , Livia Maria Marques Pereira; , Elton Santos Guedes de Morais; , Anísio Francisco Soares (Archives of Current Research International, 2024)
The horse is a large, strong, docile, and easily handled animal with therapeutic qualities, making it an ideal experimental model for various studies. Given this, the aim of this review is to identify the criteria for selecting horses as an experimental model in research related to equine-assisted therapy (hippotherapy), antivenom production, and equestrian sports. To achieve this, a bibliographic search was conducted in the Google Scholar database using the following keywords: “selection,” “horses,” “equine-assisted therapy,” “equestrian sports,” and “antivenom.” Inclusion criteria focused on selecting articles that provided relevant and insightful information on these search terms. The analyzed studies demonstrated that equine-assisted therapy is an effective therapeutic approach for the rehabilitation of individuals with disabilities, fostering improvements in motor, cognitive, and emotional aspects. In selecting horses for equine-assisted therapy, motor, morphological, and behavioral criteria were considered to ensure both the safety and effectiveness of treatment. For antivenom production, large horses were preferred due to their greater blood volume, which enables better tolerance during plasma collection. Lastly, in selecting horses for equestrian sports, it was noted that each breed possesses specific skills suited to different sport categories; thus, criteria such as obedience, physical endurance, and agility were assessed for each horse.